2017
DOI: 10.1039/c7cc01045a
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh volatile iodine uptake by hollow microspheres formed from a heteropore covalent organic framework

Abstract: We herein report the construction of a new heteropore COF which consists of two different kinds of micropores with unprecedented shapes. It exists as hollow microspheres and exhibits an extremely high volatile iodine uptake (up to 481 wt%) by encapsulating iodine in the inner cavities and porous shells of the microspheres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(136 citation statements)
references
References 32 publications
4
126
0
3
Order By: Relevance
“…After iodine uptake, new strong iodine peaks were detected beside the original ones. This result is consistent with the observation by Yin et al . The iodine molecules being encapsulated by the PAN4 was further evidenced by EDX element mapping, which revealed that the iodine was well dispersed in the whole porous sample (Figure S8).…”
Section: Resultssupporting
confidence: 92%
“…After iodine uptake, new strong iodine peaks were detected beside the original ones. This result is consistent with the observation by Yin et al . The iodine molecules being encapsulated by the PAN4 was further evidenced by EDX element mapping, which revealed that the iodine was well dispersed in the whole porous sample (Figure S8).…”
Section: Resultssupporting
confidence: 92%
“…No further change in the amount was observed after 60 min, indicating that the system was saturated and the uptake reached up maximum. The weight gain of iodine was 4110 mg g −1 for PG‐800, 3460 mg g −1 for PG‐700, and 2460 mg g −1 for PG‐600, much higher than that of graphene (1700 mg g −1 ) and other solid adsorbents,,,,, (Table ). To our best knowledge, the iodine uptake for PG‐800 is the highest value for the carbon‐based solid adsorbents reported to date ,.…”
Section: Resultsmentioning
confidence: 91%
“…SIOC-COF-7 (Figure 54 d) has been reported to adsorb iodine with acapacity that is much higher than the theoretical capacity based on the pore volume. [230] This effect likely originates from adsorption on the surface of the COF materials rather than the porous space of the COFs.…”
Section: Angewandte Chemiementioning
confidence: 99%